2018
DOI: 10.1038/s41598-018-33078-7
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of alternative splicing in Capra_hircus

Abstract: Alternative splicing (AS) is a fundamental regulatory process in all higher eukaryotes. However, AS landscapes for a number of animals, including goats, have not been explored to date. Here, we sequenced 60 samples representing 5 tissues from 4 developmental stages in triplicate using RNA-seq to elucidate the goat AS landscape. In total, 14,521 genes underwent AS (AS genes), accounting for 85.53% of intron-containing genes (16,697). Among these AS genes, 6,342 were differentially expressed in different tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The TruSeq Stranded mRNA LT Sample Prep Kit (Illumina, RS-122-2101) was used for the construction of 18 cDNA libraries [ 24 ], and the Illumina sequencing platform (HiSeqTM 2500) was used to sequence these libraries, generating 125 bp paired-end reads [ 25 , 26 ]. Raw data underwent recognition analysis to obtain original sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…The TruSeq Stranded mRNA LT Sample Prep Kit (Illumina, RS-122-2101) was used for the construction of 18 cDNA libraries [ 24 ], and the Illumina sequencing platform (HiSeqTM 2500) was used to sequence these libraries, generating 125 bp paired-end reads [ 25 , 26 ]. Raw data underwent recognition analysis to obtain original sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…DYSF mutations are associated with muscular dystrophy in humans (Bashir et al, 1998) and mice (Bittner et al, 1999). DYSF has also been identified as an alternatively spliced gene in goat leg muscle, likely playing crucial roles in skeletal muscle development (Xu et al, 2018). A study has revealed several candidate genes associated with goat ear morphology (Brito et al, 2017).…”
Section: Genomic Characteristics Of the Chongming White Goat Breedmentioning
confidence: 99%